Comparative Analysis of Trigeminal Neuralgia Caused by Sole Arterial and Venous Compression: Clinical Features and Surgical Outcomes From 222 Cases - Wang, Junwen; Niu, Hongquan; Zhao, Kai; Shu, Kai; Lei, Ting (Frontiers in Neurology, 2021)
Background: Compared with trigeminal neuralgia (TN) caused by arterial neurovascular conflict (NVC), the clinical characteristics and managements for TN with venous NVC are not well-established. This study aims to comparatively summarize the clinical features and surgical outcomes of microvascular decompression (MVD) for patients with TN caused by sole arterial and venous compression, with a particular focus on the morphological features of posterior cranial fossa (PCF). Methods: A total of 222 patients with TN caused by sole arterial NVC (188/84.7%) and venous NVC (34/15.3%) underwent MVD in our department from January 2014 to December 2018. The patient data were analyzed retrospectively. Particularly, we focused on the potential impact of PCF on surgical outcomes. Results: Compared with arterial NVC, V3 branch of the trigeminal nerve was more frequently involved in venous NVC (p = 0.009). The most common compression site was root entry zone for arterial NVC (68.6%) and midcisternal segment for venous NVC (76.5%) (p < 0.001). No serious post-operative complication was observed in the two groups. Both short- and long-term outcomes were relatively worse in venous NVC cases compared with arterial NVC cases (p = 0.001 and p = 0.030, respectively); and a dominantly higher rate of delayed cure was demonstrated in venous NVC cases (p < 0.001). TN patients with venous NVC revealed a more flat-shaped PCF than those with arterial NVC. Moreover, flat-shaped PCF morphometry was negatively correlated with surgical outcomes of TN patients with arterial NVC, but not with those of venous NVC cases. Conclusions: MVD is an effective and safe treatment for patients with TN caused by either arterial or venous NVC. Patients with a more flat-shaped PCF might be vulnerable to venous compression. Our study demonstrated that PCF morphometry only affected the surgical outcomes of patients with TN caused by arterial NVC, but not the outcomes of those with venous NVC.